Advancement in fingerprint identification over the last decade - Himali Upadhyay (International Journal of Medical Toxicology and Legal Medicine, 2024)
Fingerprints play a significant part in criminal identification. The development of latent fingerprints is a crucial phase in the whole process of fingerprint recognition. For many years, many chemical and metal powders have been utilized in the field of Forensic Science. However, there are novel methodologies emerging from the realm of green chemistry. This article examines advancements in fingerprint creation and recognition.